Revision of Mesothymbris Evans, 1956, from the Late Triassic of Mount Crosby, Queensland (Hemiptera: Cicadomorpha: Hylicelloidea: Hylicellidae) - Lambkin, Kevin J. (Zootaxa, 2019)
New specimens and a re-examination of their holotypes have clarified the status of five species of the extinct cicadomorphan family Hylicellidae from the Late Triassic (Norian) Mount Crosby Formation of south-eastern Queensland. All were found to be conspecific, resulting in the following synonymies: Mesothymbris Evans, 1956 (= Triassoscytina Evans, 1956, syn. nov. = (in part) Triassoscytinopsis Evans, 1956, syn. nov.), Mesothymbris perkinsi Evans, 1956 (= Mesothymbris woodwardi Evans, 1956, syn. nov. = Triassoscytina incompleta Evans, 1956, syn. nov. = Triassoscytinopsis stenulata Evans, 1956, syn. nov. = Triassoscytinopsis aberrans Evans, 1956, syn. nov.). The Hylicellidae is still poorly defined as is its generic composition. Mesothymbris, however, is clearly distinct from the other Mount Crosby hylicellids, Hylicella Evans, 1956, and Triassocotis, Evans, 1956, in the quite distal primary fork of R, the angled RA at the point of separation of RA1 with RA2 directed towards the apex of the tegmen, the upright RA1, the shape of the intra-medial cell, and CuA just distal to the basal cell strongly curved and very closely approximating the claval suture. The new synonymies further clarify the composition of the cicadomorphan fauna of the Mount Crosby Formation, which as a result of this and other recent revisions, now comprises 16 nominal species in the Dysmorphoptilidae, Hylicellidae and Mesojabloniidae, as well as three species incertae sedis. In the presence of Dysmorphoptilidae and Hylicellidae, the Mount Crosby cicadomorphan fauna is similar to that of the younger Late Triassic Blackstone Formation at nearby Denmark Hill and Dinmore. It differs significantly, however, in the absence, after 90 years of collecting of 100s of specimens, of any representatives of the Dunstaniidae, Mesogereonidae, or Tettigarctidae, families so characteristic of the Denmark Hill/Dinmore fauna. Whether this difference is biogeographical, ecological, or simply as a result of differential preservation is unknown.